Seasonal data on Rose Bengal stained foraminifera in the head of Kongsfjorden, Svalbard - Olga Kniazeva (Data in Brief, 2019)
Current ‘Atlantification’ of the Arctic Ocean affects benthic communities leading to the changes in their structure and abundance. Such areas as Svalbard that are seasonally affected by Atlantic and Arctic water masses may give a possibility to preliminary estimate the response of benthic communities to short-term environmental changes and to evaluate their sensitivity. We have sampled Kongsfjorden for modern benthic foraminifera in three different seasons. The record includes data on the abundances of benthic foraminiferal species in the surface sediments (0–2cm). This data gives an insight into the seasonal dynamics of the near-glacial foraminiferal community of Kongsfjorden. Keywords: Benthic foraminifera, Arctic fjord, Seasonal dynamics